Pengaruh Mobilisasi Dini Terhadap Frekuensi Mual Muntah Pada Pasien Post Laparatomi di RS Kanker Dharmais Jakarta - Laily Maftuhah; Yuni Susilowati; Dewi Nur Puspitsari (Medical Laboratory Journal, 2023)
Background: Major surgery is a method of treatment that is most often performed to treat a medical condition or disease. World Health Organization (WHO) in 2020 the worlds laparratomy patients increase every year until 10%. In Indonesia, laparotomy cases are ranked 5th, it is recorded that the total number of operationsthere are1.2 milion peoplesand an estimated 42% of them are laparotomy surgeries. Nausea and vomiting are the two most common postoperative side effects. Early mobilization exercises can have an effect on reducing postoperative nausea and vomiting in anesthetized patients. Objective: to determine the effect of early mobilization on the frequency of nausea and vomiting due to anesthesia in post-laparotomy patients at Dharmais Cancer Hospital, Jakarta. Research Method: pre-experimental design with one group pretest posttest design. The sample size of this study was 56 post-laparotomy patients using a purposive sampling technique. Data analysis using Wilcoxon test. Results: nausea, vomiting before early mobilization in large post-laparotomy patients, mild nausea (50.0%) and after early mobilization, most of them were not nauseous (53.6%). Bivariate analysis with the Wilcoxon test obtained p-value: 0.000 (α: <0.05). Conclusion: There is an effect of early mobilization on the frequency of nausea and vomiting due to anesthesia in post-laparotomy patients at Dharmais Cancer Hospital, Jakarta.